Determinants of a bank's profitability with the mediating role of interest rate spread: A case of Vietnam - Quy, Vo Thi; Tuan, Pham Dang (Asian Economic and Financial Review, 2024)
Considering the fundamental function of commercial banks in the economy, which involves the facilitation of fund transfers from lenders to borrowers, it is imperative for these institutions to carry out this task in a manner that is both efficient and effective. This is crucial to fostering economic growth and enhancing social welfare. A bank's profitability has been a subject of scrutiny by researchers in many countries for decades. This study aims to analyze the impact of interest rate spread (IRS) and its mediating role in the relationship between bank-specific factors and the bank's profitability at the Commercial Bank of Vietnam. The data was collected from 2008 to 2020 for the 25 Commercial Banks using panel regression. The study found the positive effect of cost efficiency (CE), income diversity (ID), and liquidity risk (LIQ) on the IRS; however, bank size (BS), non-performing loan (NPL), provision of bad and doubtful debts (PL), asset structure (AS), non-interest expense (NIE), and economic conditions (ECD) do not impact the IRS statistically significantly. The study also confirms the IRS's mediating role. The study findings provide empirical evidence of the explaining and mediating role of the IRS on bank profitability. This study recommends that policymakers encourage Commercial Banks to diversify their income in order to avoid focusing on traditional activities, which can lead to credit overheating.